Die Wahrheit erfinden?: eine Skizze zum fruchtbaren Spannungsverhältnis von Offenbarung und Fiktionalität - Seip, Jörg (Zeitschrift für katholische Theologie, 2002)
To invent truth? On the base of this question the article discusses the straines and fruitful relation between fictionality as a characteristic dimension of literature and revelation as a selfcommunication of god. It is important that the terms "fictionality" and "fictional" are not identical with fiction or fictitions. Two interpretations of fictionality are explained: the first (Petersen) is founded on the clear distinction of real and fictional states. The second one (Anderegg, Iser, Haug) can be defined as a construction of sense in the medium of literature. The bible as literature contains just so fictional texts. On this background finally the relation between fictionality and revelation is discussed also the question of conclusion or non-conclusion of divine revelation in holy scripture and tradition.